2009
DOI: 10.1099/ijs.0.003160-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbacterium binotii sp. nov., isolated from human blood

Abstract: Two strains of non-spore-forming, rod-shaped, Gram-positive bacteria, CIP 101303 T and CIP 102116, were isolated from human blood in 1976 and 1977, respectively. These strains had chemotaxonomic markers that were consistent with classification in the genus Microbacterium, i.e. MK-10, MK-11 and MK-12 as the major menaquinones, predominant iso-and anteiso-branched cellular fatty acids, galactose, mannose and rhamnose as the cell-wall sugars and ornithine as the diamino acid in the cell-wall peptidoglycan. The DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…The PCR-amplified 16S rDNA fragments were purified using a PureLink ® PCR Purification Kit (Invitrogen TM , USA) according to the manufacturer's instructions and evaluated afterwards by electrophoresis in a 1% agarose gel. Table 2 shows the primers used for each sequencing reaction (Clermont et al, 2009). For each sequencing reaction, a mixture was made of 1 μl of purified PCR product, 0.5 μl of the Big Dye TM Termination Ready Reaction Mix (Applied Biosystems), 3.75 μl sterile Milli-Q water and 3 μl (20 ng μl -1 ) of one of the eight sequencing primers used.…”
Section: S Rrna Gene Amplification Purification and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR-amplified 16S rDNA fragments were purified using a PureLink ® PCR Purification Kit (Invitrogen TM , USA) according to the manufacturer's instructions and evaluated afterwards by electrophoresis in a 1% agarose gel. Table 2 shows the primers used for each sequencing reaction (Clermont et al, 2009). For each sequencing reaction, a mixture was made of 1 μl of purified PCR product, 0.5 μl of the Big Dye TM Termination Ready Reaction Mix (Applied Biosystems), 3.75 μl sterile Milli-Q water and 3 μl (20 ng μl -1 ) of one of the eight sequencing primers used.…”
Section: S Rrna Gene Amplification Purification and Sequencingmentioning
confidence: 99%
“…T h e 1 6 S r R N A g e n e o f i s o l a t e s w a s amplified with the conserved primers: ARI C/T (5'CTGGCTCAGGAC/TGAACGCTG3') and pH (5'AAGGAGGTGATCCAGCCGCA3') (Clermont et al, 2009), which amplify almost the full length of the 16S rRNA gene (1500 bp). Each 50 μl amplification reaction contained: 5 μl dNTPs (2 mM of each), 5 μl GeneAmp 10X-PCR buffer (100 mMTris-HCl (pH 8.3)), 500 mM KCl, 15 mM MgCl 2 , 0.01% (w/v) gelatin), 0.5 μl of each primer (50 ng μl -1 ), 1 μl AmpliTaq DNA polymerase (1 U μl -1 ), 34.5 μl Milli-Q water and 5 μl of template (DNA extracted from isolated colonies).…”
Section: S Rrna Gene Amplification Purification and Sequencingmentioning
confidence: 99%
“…Sequencing and phylogenetic analysis of the 16S rRNA gene of all type strains of the collection were done as described by Clermont et al (2009). The sequences were transferred to the LTP database [Living Tree Project (Yarza et al, 2008) release 100, September 2009] within the ARB software environment (Ludwig et al, 2004), aligned to the lactobacilli sequences present in LTP and checked for identity.…”
mentioning
confidence: 99%
“…Gasser later showed that the mobility of the lactic dehydrogenase enzyme used as a tool to identify Lactobacillus species was consistent within strains of a single species, but that some strains such as 61D T also showed variation (Gasser, 1970). Unfortunately, the history of strain 1517 T is not known.The strains were cultivated under anaerobic conditions in MRS agar or broth at 37 u C and have been conserved in a freeze-dried condition since the early 1980s.Sequencing and phylogenetic analysis of the 16S rRNA gene of all type strains of the collection were done as described by Clermont et al (2009 .4 %, respectively). Levels of similarities were above 97 %, and therefore DNA-DNA hybridization was performed according to Stackebrandt & Goebel (1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation